Epigallocatechin gallate in combination with eugenol or amarogentin shows synergistic chemotherapeutic potential in cervical cancer cell line. Issue 1 (4th August 2018) - Pal, Debolina; Sur, Subhayan; Roy, Rituparna; Mandal, Suvra; Kumar Panda, Chinmay
Abstract : In this study, antitumor activity of epigallocatechin gallate (EGCG; major component of green tea polyphenol), eugenol (active component of clove), and amarogentin (active component of chirata plant) either alone or in combination were evaluated in Hela cell line. It was evident that EGCG with eugenol–amrogentin could highly inhibit the cellular proliferation and colony formation than individual treatments. Induction of apoptosis was also higher after treatment with EGCG in combination with eugenol–amrogentin than individual compound treatments. The antiproliferative effect of these compounds was due to downregulation of cyclinD1 and upregulation of cell cycle inhibitors LIMD1, RBSP3, and p16 at G1/S phase of cell cycle. Treatment of these compounds could induce promoter hypomethylation of LimD1 and P16 genes as a result of reduced expression of DNA methyltransferase 1 (DNMT1). Thus, our study indicated the better chemotherapeutic effect of EGCG in combination with eugenol–amarogentin in Hela cell line. The chemotherapeutic effect might be due to the epigenetic modification particularly DNA hypomethylation through downregulation of DNMT1. Abstract : Eugenol–amarogentin treated with epigallocatechin gallate (EGCG) showed better chemotherapeutic effect. Treatment with three Individual compound as well as combined treatment (i.e., eugenol + EGCG or amarogentin + EGCG) both induced promoter hypomethylation of LIMD1 and P16. This hypomethylation is due to downregulation of DNA methyltransferase 1 by both treatment types